New trends in prevention and treatment of postpartum mastitis and lactostasis - A. A. Balushkina; V. L. Tyutyunnik; N. E. Kan; O. A. Pustotina; G. V. Moskaleva (Медицинский совет, 2019)
Exclusive breastfeeding in the first 6 months of life is recommended by the World Health Organization, since breast milk provides the baby with all the nutrients and elements necessary for normal development and growth. In the first weeks of lactation, women can often face a number of problems, such as pain in the breasts and nipples, nipple cracks and mastitis. These problems make feeding difficult and, in some cases, lead to the cessation of breastfeeding. Mastitis is a terrible complication of the postpartum period and the basis for the cessation of lactation. Counseling and support of mothers, prevention of lactostasis, nipple cracks and teaching techniques to properly attach the child, reduce the complications of lactation. Timely diagnosis and adequate therapy of mastitis, helps to preserve breastfeeding and improve the health of the mother and child.